Penyalahgunaan Narkotika Serta Upaya Pencegahan dan Penanggulangannya - Nita Ganap; Stella Maindoka; Johanis L. S. S. Polii; Rinny Ante; Grenaldo Ginting (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
How does the law relate to drug abuse? How does North Sulawesi handle and combat drugs? Research, also known as research, is a very educationally beneficial search effort because it teaches us to always be aware that we still do not know much about this world. What we search for, find, and know may not be completely true, because it still needs to be tested again. The method is the main way to achieve a goal, to achieve the expected level of accuracy, quantity, and type. Secondary data sources, consisting of primary, secondary, and tertiary legal materials, are used as normative legal research methods. To tighten supervision of the distribution and use of drugs, several laws have been made, such as Law No. 35 of 2009 concerning Narcotics. For users who qualify as victims of addiction, the justice system is expected to act not only repressively but also rehabilitatively. The use of legal sanctions together with a rehabilitation approach is considered more effective in combating the chain of drug abuse. In legal efforts to prevent and stop drug abuse, there are primary prevention, secondary prevention, and tertiary prevention. All people and levels of society, such as parents, teachers, and lecturers at schools and the entire community, can carry out prevention and control in various ways. Efforts to control drug abuse must be directed at prevention, strict but fair law enforcement, and recovery for users through rehabilitation.